Eye-tracking Study of Reading Speed from LCD Displays: Influence of Type Style and Type Size - Gregor Franken; Anja Podlesek; Klementina Možina (Bern Open Publishing, 2015)
Increasing amounts of text are read from various types of screens. The shape and the size of a typeface determine the legibility of texts. The aim of this study was to investigate the legibility of different typefaces displayed on LCD screens. Two typefaces (Georgia and Verdana), designed for screen renderings were analyzed by eye-tracking technology in 8 different sizes. Regardless of the font size, the texts set in Verdana were read faster. For both typefaces the reading speed increased with increasing the font size. The number of fixations increased with the character size, while the fixation time was shorter.